2019
DOI: 10.1056/nejmoa1809798
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Methotrexate for the Prevention of Atherosclerotic Events

Abstract: BACKGROUND Inflammation is causally related to atherothrombosis. Treatment with canakinumab, a monoclonal antibody that inhibits inflammation by neutralizing interleukin-1β, resulted in a lower rate of cardiovascular events than placebo in a previous randomized trial. We sought to determine whether an alternative approach to inflammation inhibition with low-dose methotrexate might provide similar benefit. METHODS We conducted a randomized, double-blind trial of low-dose methotrexate (at a target dose of 15 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
756
6
14

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,010 publications
(784 citation statements)
references
References 26 publications
8
756
6
14
Order By: Relevance
“…For example, one potential anti‐inflammatory that is currently used in the treatment of rheumatoid arthritis is methotrexate . However, the CIRT (Cardiovascular Inflammation Reduction Trial) trial of low‐dose methotrexate failed to reduce the incidence of cardiovascular events in patients with hyperglycemia and high levels of CRP . Additionally, the highly anticipated lipoprotein‐associated phospholipase A2 inhibitor darapladib failed to reduce cardiovascular risk in two separate clinical trials; STABILITY (Stabilization of Atherosclerotic Plaque by Initiation of Darapladib Therapy) and SOLID‐TIMI 52 (The Stabilisation Of pLaques usIng Darapladib‐Thrombolysis In Myocardial Infarction 52) .…”
Section: Current Anti‐atherogenic Therapies Their Limitations and Tmentioning
confidence: 99%
“…For example, one potential anti‐inflammatory that is currently used in the treatment of rheumatoid arthritis is methotrexate . However, the CIRT (Cardiovascular Inflammation Reduction Trial) trial of low‐dose methotrexate failed to reduce the incidence of cardiovascular events in patients with hyperglycemia and high levels of CRP . Additionally, the highly anticipated lipoprotein‐associated phospholipase A2 inhibitor darapladib failed to reduce cardiovascular risk in two separate clinical trials; STABILITY (Stabilization of Atherosclerotic Plaque by Initiation of Darapladib Therapy) and SOLID‐TIMI 52 (The Stabilisation Of pLaques usIng Darapladib‐Thrombolysis In Myocardial Infarction 52) .…”
Section: Current Anti‐atherogenic Therapies Their Limitations and Tmentioning
confidence: 99%
“…In other circumstances, apparent discrepancies between RCTs and RWE studies may be attributable to different patient populations or different measurement approaches, making a direct comparison less meaningful. Several RWE studies of RA patients have suggested potential CV benefits from treatment with methotrexate , which were discordant with the findings from the Cardiovascular Inflammation Reduction Trial (CIRT), which found no CV benefits from methotrexate . However, CIRT did not include any patients with RA or patients with any other systemic inflammatory diseases, resulting in a study population of patients with minimal systemic inflammation and a median C‐reactive protein level of 1.5 mg/liter.…”
Section: What Can We Learn From Comparing the Current Rct To Thesementioning
confidence: 84%
“…68 Vaccination with ox-LDL as a therapeutic strategy for atherosclerosis remains an elusive approach in humans 7 while a clinical trial of intravenous immunoglobulin, which contains natural anti-ox-LDL antibodies, seems to exert anti-atherogenic role. 70 Similarly, TNF blockade seems to confer protection against atherosclerosis in RA patients. 60 Additionally, methotrexate treatment seems to reduce and CV events in patients with underlying rheumatic diseases such as rheumatoid arthritis (RA) and psoriasis, but not in those with coronary disease and concomitant type 2 Diabetes Mellitus (DM) or metabolic Syndrome.…”
Section: Immunomodulatory Agents Are Not Effective In the Therapy Ofmentioning
confidence: 99%